(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes modern design methods used in the production of special clothing, in particular, items used for medical purposes. As a result of the development of digital technologies, the possibilities of 3D modeling, virtual clothing testing, creating precise designs, and optimizing ergonomic design solutions are increasing. The study examines the functional capabilities of CLO 3D, Marvelous Designer, and traditional 2D design programs, their influence on production efficiency, and their role in simplifying technological processes. Also, the advantages of digital design in improving the quality of special clothing, reducing production time, and ensuring the compatibility of the product with human anatomy are scientifically substantiated. The obtained results indicate the importance of modern design approaches in the production of special clothing.